RANCANG BANGUN MEDIA PERMAINAN MONOPOLI EDUKATIF“MERKAYASA” UNTUK MENANAMKAN KARAKTER TOLERANSI DALAM PEMBELAJARAN IPS - Cindy Kusuma Putri; Umar Umar; Muh. Husen Arifin (Universitas Tanjungpura, 2022)
This research is motivated by the lack of interesting and fun learning media in carrying out the learning process and inculcating the value of the character of tolerance to students. The use of fun learning media is currently very much needed as an effort to overcome student boredom with conventional methods carried out by teachers during the learning process, especially in social studies learning in elementary grade IV. The purpose of this study is to produce learning media in the form of the educational monopoly game